DINAMIKA DAN RESOLUSI KONFLIK GAJAH SUMATERA (Elephas maximus sumatranus ) TERHADAP MANUSIA DI KECAMATAN MANDAU KABUPATEN BENGKALIS - Nuryasin '; Defri Yoza; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Changing the functions of forest areas in Balai Raja became farmland, plantations and settlements is a major factor in the occurrence of Human-Elephant Conflict. This research aims to identify the typology of Human-Elephant Conflict, to know the success of efforts to overcomingthe Human-Elephant Conflict which has been applied and to calculate the economic losses as a result of Human-Elephant Conflict on Petani and Balai Makam villages. The method used consisted of survey methods toward the ravages of Human-Elephant Conflict and interviews to the people who are in conflict with elephants. The results showed that there are 4 Elephant-Human Conflict typology: Elephants damaging crops, damaging the elephant hut community, the elephants attacked human and human kill the elephants. Various efforts have been undertaken, but the results have not been able to resolve conflicts of an elephant for the long term. Attempts at countermeasures which were undertaken are only able to tackle the conflict of elephants in a while. As a result of Human-Elephant Conflict, it resulted in economic losses either directly or indirectly. The desired people efforts in resolving the conflicts of human-elephant is to move the elephants from the scene of the conflict. Human-Elephant Conflict resolution can be done by restore the status of Balai Raja that is habitat of elephants. Conflict resolution in the long term can be done with the elephant habitat management with enriching germplasm that can serve as the source of the feed elephants.   Key words: Dynamics, conflict, conflict resolution, conflict prevention.